The Great Reduction of Equatorial Electrojet During the Solar Eclipse on 14 December 2020 - Kedeng Zhang; Hui Wang (Space Weather)
Abstract The solar eclipse has a great influence on the variability of the ionosphere because of the obscuration of solar radiation. Using the equatorial electrojet (EEJ) and plasma measurements from Swarm, zonal winds from the Michelson Interferometer for Global High‐resolution Thermospheric Imaging on Ionospheric Connection Explorer mission, and electron density from the Constellation Observing Systems for Meteorology, Ionosphere, and Climate mission, the temporal responses of EEJ to the total solar eclipse on 14 December 2020, have been examined. In comparison with non‐eclipse EEJ, EEJ at the eclipse/early post‐eclipse phase is significantly reduced, with a percentage of more than 29%. The reduced EEJ is primarily attributed to both the weakened electric field and the reversed zonal winds. The reversed zonal winds could drive corresponding currents and electric field, indicating the direct and indirect roles. The depleted plasma plays a secondary role in the decrease of EEJ.